Lessons to be learned: The knowledge, attitudes, and practices of Turkish people towards the COVID-19 pandemic - Bener, Abdulbari; Atak, Muhammed; Morgul, Ebru; Barışık, Cem Cahit (Wolters Kluwer Medknow Publications, 2022)
Background: The world experienced the greatest pandemic of the 21 st century with the emergence of a new and readily transmissible the coronavirus disease. Understanding knowledge, attitudes, and practices (KAP) of the public towards the pandemic is an essential part of developing effective preventive strategies. Aim: The objective of this study was to investigate the knowledge, attitudes, and practices (KAP) concerning the coronavirus (COVID-19) among population in Istanbul. Methods: This is a cross-sectional and multi-stage, stratified random sampling based on multi-center population of Istanbul. A total of 5,414 persons were contacted and 4361 participants (80.5%) gave consent. The data were analyzed using descriptive and multiple regression analyses. Results: There were significant differences between low education and high educational level with respect to age groups, gender, occupation, income, residence, number of rooms and family members (P < 0.001). Responses concerning knowledge of COVID-19 indicated that subjects with high education level were significantly higher regarding knowledge of the signs and symptoms of COVID-19 and methods of detecting COVID-19 respectively. Majority of the participants consider COVID-19 risk is higher than AIDS or Cancer (75.8% of low education vs. 67.2% of high education level (P < 0.001). Multivariate stepwise regression analysis revealed that monthly income status (P < 0.001), appropriate method of detecting COVID-19 (P < 0.001), occupational status (P < 0.001), medical mask prevent against COVID-19 (P < 0.001), eating or contacting wild animals (P < 0.001), isolation and treatment of people reduce risk (P < 0.001), isolation 14 days (P < 0.001), avoid going to crowded places such as train-metro, bus, restaurants and shopping (P = 0.003), COVID-19 spreads via-respiratory droplets (P = 0.004), afraid of travel (P = 0.026) were significantly associated with COVID-19 knowledge. Conclusions: The current study results revealed that the educational level and occupation especially sedentary are correlated positively with knowledge, attitude and practices. This finding is not surprising since higher education levels and professional status are associated with good KAP in most epidemic diseases including COVID-19. Nevertheless, the recent experience with COVID-19 has provided lessons on strategy and policy making.
Keywords: COVID-19; Istanbul; KAP Study; Pandemic; Public Health; Surveys